The Impact of Smartphone Dependence on Student Personality in Malang - Saputra, Irzan Tri; Aziz, Jordan Abdul; Fathurrozi, M. Iqbal; Priambodo, Septian Putra; Nur, Hasanah (Letters in Information Technology Education (LITE), 2019)
Cellphones are the most popular communication devices perceived today. Students use smartphones as communication and entertainment to avoid stress. Excessive use of smartphones with high intensity can cause dependence. Smartphone dependence has a negative influence on quality of life and health such as anxiety. Indication of anxiety disorders can be physical, psychological, and behavioral.